Relation between perinatal outcome and gestational duration in term primiparous pregnancies stratified by body mass index. (27th September 2022) - Lindegren, Lina; Stuart, Andrea; Herbst, Andreas; Källén, Karin
Abstract: Introduction: There is growing evidence that induction of labor at 41 completed weeks improves neonatal outcome, at least among primiparous women. This study was performed to investigate whether maternal body mass index (BMI) should be considered when deciding on timing of intervention in term pregnancies. Material and methods: The study design was a historical cohort study using data from the Swedish Medical Birth Register, singletons in cephalic presentation with births 39+0 to 41+6 weeks, with available information on maternal BMI 2005–2017 ( n = 352 567). Modified Poisson regression analyses were used to investigate the association between gestational duration and stillbirth or death before 45 postmenstrual weeks (primary outcome) and Apgar score <7 at 5 minutes (secondary outcome) by BMI, respectively. Adjustments were made for maternal age, smoking, country of birth and educational level. Results: The adjusted relative risk (ARR) of stillbirth or death before 45 weeks among infants born at 41+0 to 41+6 vs 40+0 to 40+6 weeks, was 1.26 with a 95% confidence interval (CI) of 1.07–1.48. Among women with BMI ≥30, the offspring mortality risk in pregnancies lasting 39+0 to 39+2 weeks was significantly above the corresponding risk among women of normal BMI who delivered at 41+0 to 41+2 weeks (ARR = 1.95; 95% CI 1.07–3.56) but no statistically significant heterogeneity was found regarding the magnitude of the association between gestational duration and offspring mortality. The ARR, for Apgar <7 at 5 minutes (41+0 to 41+6 vs 40+0 to 40+6 weeks, regardless of BMI), was 1.36 (95% CI 1.27–1.45). The risk for low Apgar score at 41+0 weeks was 1.5% among all children regardless of maternal BMI. Among children to women with BMI ≥30, this magnitude of risk was found already at 39+3 weeks. Conclusions: In primiparous women with obesity the risk of stillbirth or death before 45 postmenstrual weeks were increased throughout all full‐term gestational age categories, compared with women with overweight or normal BMI. Children to obese women had the same risk for Apgar scores <7 at 5 minutes compared with women overall at earlier gestational age. The results suggest that maternal BMI needs to be considered when discussing timing of elective induction in term healthy pregnancies of primiparous women. Abstract : In primiparous women with obesity the risk of stillbirth or death before 45 postmenstrual weeks were increased throughout the entire study period, gestational week 39+0 ‐ 41+6, compared to women with overweight or normal BMI. Children to obese women had the same risk for Apgar score <7 at 5 minutes at an earlier gestational age compared to women overall. The results suggest that maternal BMI needs to be considered when discussing timing of elective induction in term healthy pregnancies of primiparous women.